Clicking vs. sharing: The relationship between online news behaviors and political knowledge. (June 2016) - Beam, Michael A.; Hutchens, Myiah J.; Hmielowski, Jay D.
Abstract: Online news and social media are transforming the process of news production and reading. While research has shown that news media play an important role in providing information to the public in democratic societies, research investigating the impact of sharing news online on the process of public opinion formation is in a nascent stage. This study examines the impact of viewing and sharing online news on two dimensions of political knowledge: factual knowledge and structural knowledge. Results from survey data collected over 3-waves during the 2012 US Presidential Election from an online panel of 403 US adult Internet users show that reading online news is positively related to factual political knowledge. Sharing online news, in contrast, is related to structural knowledge. We discuss these findings and their implications for future research investigating the role of online news. Highlights: We examined the relationship between online news behaviors and political knowledge. We collected three-wave survey data from 403 adults during the 2012 US election. People who share news online are also reading news online. Online news reading was positively related to factual political knowledge. Online news sharing was positively related to political knowledge structure density.